Successful Control of Malignant Pericardial Effusion from Endometrial Cancer Using Intrapericardial Chemotherapy: A Case Report - Rodríguez, Katherine Estefania Torres; Pullupaxi, Erika Daniela Criollo; Cordonez Valle, Jair Sebastián; Arias, Fátima Belén Del Hierro; Tanquino, Patricio Andrés Granja; Jaramillo Eguez, Berenice Gabriela; Benavides Zavala, Cindy Nicole (Brazilian Journal of Case Reports, 2026)
Endometrial cancer (EC) is one of the most common gynecologic malignancies worldwide, with increasing incidence and mortality. Although metastasis typically involves lymph nodes, peritoneum, and lungs, malignant pericardial effusion (MPE) is a rare and life-threatening complication, often associated with advanced disease and poor prognosis. We report the case of a 70-year-old woman with stage IIIB endometrial adenocarcinoma previously treated with surgery, chemotherapy, and radiotherapy, who presented three years later with cardiac tamponade due to MPE. Initial management with pericardiocentesis resulted in clinical stabilization; however, early recurrence occurred within 30 days, with cytological and histopathological confirmation of metastatic carcinoma of Müllerian origin. Given the high risk of recurrence, intrapericardial chemotherapy with cisplatin was administered (10 mg/20 mL daily for five days) via a pericardial catheter. The patient tolerated the procedure well, with no significant complications or systemic toxicity. Follow-up echocardiography demonstrated complete resolution of the effusion, and the patient remained asymptomatic at one-month follow-up, without evidence of early recurrence. This case highlights the feasibility and effectiveness of intrapericardial cisplatin as a locoregional treatment strategy for recurrent MPE in selected patients. Although evidence is limited and primarily derived from observational studies, this approach may reduce recurrence rates and the need for repeated invasive procedures. Intrapericardial chemotherapy should be considered within a multidisciplinary framework, particularly in palliative settings where local control is the primary goal.